Language teachers' accounts of challenges in two European settings of integration training - Häkkinen Miira; Mikkilä-Erdmann Mirjamaija (Sage, 2022)
This study investigates the work of second language teachers in two institutional settings responsible for integration training. By exploring teachers' accounts in Finland and Germany, we seek to deepen the understanding of the daily practice of second language education. Bridging conceptual and practical approaches, the aim is to contribute to the current discourse on the development of adult second language education in Europe. A phenomenographic analysis of semi-structured interviews reveals challenges that influence instruction from inside and outside institutional practice. Accounts in the Finnish setting depict issues in how language education, teachers' work, and adult education are perceived. Administration and language teachers disagree on what needs to be improved in a changing societal environment. Professional pride and appreciation are strongly demanded in a profession that is still being established, and challenges specific to adult education translate into priorities in delivering instruction. In the German setting, expressions culminate in prerequisites, and challenges lie in the way external factors influence course design and instruction. They also touch upon learning: methods, materials, and abilities. Feelings of inadequacy describe teachers' psychological working environment. A comparison concludes a need to defend contact teaching in Finland and to improve tracking of slower learners' progress in Germany.